The influence of sport climbing joining the Olympic Games on the financial situation of the International Federation of Sport Climbing and its implications - Liu, Y. D.; Liu, L. H. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Organizational change is an important factor affecting its development. The International Federation of Sport Climbing (IFSC) contributes to the sustainable and healthy development of sport climbing and further expands the influence of sport climbing in the Olympic Games. For such a non-profit organization, good financial management is an important material basis for its long-term healthy development. Therefore, it is necessary to systematically study the economic situation of the IFSC after the entry of sport climbing into the Olympic Games, which is not only of great guiding value to the guarantee of healthy growth of the IFSC, but also of positive reference value to other international sports associations, especially for those which are looking for the entry into the Olympic Games.